Pengaruh Pendidikan dan Fasilitas Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Puskesmas Alai Kota Padang - Deani Ermanda Putri; Marta Widia Sari (Jurnal Ekonomi dan Bisnis Digital, 2026)
The purpose of this study is to determine the extent of the influence of Education and Work Facilities on Employee Performance with Job Satisfaction as an Intervening Variable at Alai Health Center, Padang City. The data analysis method used a questionnaire, with a sample of 42 respondents. The analysis method used is path analysis using the SmartPLS application. Based on the results of the study, it shows that there is a positive and significant influence of Education on Job Satisfaction. There is a positive and significant influence of Work Facilities on Job Satisfaction. There is a negative and not significant influence of Education on Employee Performance. There is a negative and not significant influence of Work Facilities on Employee Performance. There is a positive and significant influence of Job Satisfaction on Employee Performance. There is a positive and significant influence of Education on Employee Performance with Job Satisfaction as a Intervening variable. There is a positive and significant influence of Work Facilities on Employee Performance with Job Satisfaction as an Intervening Variable.